Proportional Miniaturization of Microscale Features into the Nanoscale Using Pre-stressed Polymer Films and Formation of Plasmonic Nanostructures - Abosree, Shady (My University, 2021)
Fabrication of nano structures and patterns is the basis of diverse technologies and applications in our life ranging from microelectronics and semiconductors to nanofludics, biosensors and lab-on-chip devices. However, creation of nano patterns by means of conventional nanofabrication techniques such as electron beam lithography is expensive and time consuming. Pre-stressed polymer films have been used as a miniaturization technique to fabricate features with smaller size than the initial patterned features. Microscale patterns can be miniaturized by shrinking induced due to thermal stress release of the pre-stressed films. However, there are several challenges such as lack to achieve sub-micron resolution, lack of proportional miniaturization and limited shrinkage ratio that prevent the use of current technology for effective and scalable approach to fabricate nanoscale patterns. This thesis presents development of new miniaturization approaches using shrinkable films that can proportionally miniaturize microscale patterns into nanoscale down to sub 100 nm. Low-cost, rapid and scalable method to fabricate high resolution nano patterns was demonstrated by developing a constrained shrinking process. This process was able to overcome the loss of resolution after thermal shrinking of imprinted polymer films. Moreover, the process design allowed to perform iterative miniaturization which significantly reduced the size of the initial patterns by more than 99% reduction in area. These new capabilities were applied to fabricate tunable plasmonic structures in order to demonstrate the potential of the developed miniaturization approaches that can be used in various applications including microelectronics, sensors and functional surfaces.